Análisis de la factura comercial negociable como método de financiamiento. - Vera Ferie, Mariuxi Estefania (My University, 2020)
The present investigation provides a description of the negotiable commercial invoice, and encompasses a series of substantial concepts within the study thereof. The purpose of this paper is to analyze the negotiable commercial invoice as a source of financing, thus seeking to determine its degree of reception at the national level. The methodology applied is qualitative and descriptive, where the use of bibliographic sources is used, as well as technological tools for accessing and analyzing information present in the different laws, regulations and scientific articles. The results of the investigation, after the analysis of the concepts within it, and of statistical data that comprise from the year 2015 to the year 2018 allows us to conclude in the importance, relevance, and reception of the negotiable commercial invoice within our country.
La presente investigación proporciona una descripción de la factura comercial negociable, y engloba una serie de conceptos sustanciales dentro del estudio de la misma. El presente trabajo tiene por objetivo analizar la factura comercial negociable como fuente de financiamiento, buscando de esta forma determinar su grado de acogida a nivel nacional. La metodología aplicada tiene carácter cualitativo y descriptivo, donde se recurre al uso de fuentes bibliográficas, y herramientas tecnológicas para el acceso y análisis de información presente en las diferentes leyes, reglamentos y artículos científicos. Los resultados de la investigación, posterior al análisis de los conceptos dentro de esta, y de datos estadísticos que comprenden desde el año 2015 hasta el año 2018 permite concluir en la importancia, la relevancia, y el recibimiento de la factura comercial negociable dentro de nuestro país.
Keywords: FACTURA COMERCIAL; FACTURA COMERCIAL NEGOCIABLE; FINANCIAMIENTO